2018
DOI: 10.4236/ajps.2018.96095
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Leaf Area Estimation for Arabica Coffee (<i>Coffea Arabica</i> L.) Grown at Different Altitudes of Mana District, Jimma Zone

Abstract: This study was aimed at establishing allometric models for estimating LA (Leaf Area) of eight Coffea arabica genotypes in Mana district of Jimma Zone Oromia Regional State, South Western Ethiopia (7˚46'N, 36˚0'E). Many Methodologies and instruments have been devised to facilitate measurement of leaf area. However, these methods are destructive, laborious and expensive. For modeling leaf area, leaf width, leaf length and leaf area of 1200 leaves (50 leaves for each genotype) was measured for model calibration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…They are particularly important for species that grow in harsh or unstable habitats, like F. przewalskii. Leaves have essential roles in plant physiology and long-term adaptation to environmental changes [19]. Leaf and bulb morphology and biomass accumulation are fundamental plant functional traits.…”
Section: Introductionmentioning
confidence: 99%
“…They are particularly important for species that grow in harsh or unstable habitats, like F. przewalskii. Leaves have essential roles in plant physiology and long-term adaptation to environmental changes [19]. Leaf and bulb morphology and biomass accumulation are fundamental plant functional traits.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering these two equations, the quadratic model presented values of mean absolute error (MAE) and root mean square error (RQME) closest to zero, in addition to the value of the index d closest to the unit, which suggests a more predictive leaf area of Coffea dewevrei by this model. Notoriously, several authors have reported in the literature models of mathematical equations that estimate the leaf area of several coffee varieties [15,18,29,16]. In specific cases, the model adjusted for a given variety can be used to estimate leaf area of other varieties [30].…”
Section: Resultsmentioning
confidence: 99%
“…However, the indirect and nondestructive methods allow successive evaluations in the same plant and rapidity in the evaluations [12], and are therefore more convenient and cheaper [13]. In the indirect methods, portable automatic planimeters are used, sometimes with the disadvantage that the larger leaves cannot be evaluated by limiting the reading area of the portable equipment [14], it is still used mathematical models, using leaf blade length and width [12], to which they generally involve the use of regression equations, as in Coffea arabica coffee trees [15,11,16], and Coffea canephora [17,15,18], however, in the literature there is no evidence of studies with Coffea dewevrei, therefore, it is important to obtain them, since it is known that temporal variation of leaf area in an agricultural crop depends on cultivar, edaphoclimatic conditions, and population density, among other factors [19].…”
Section: Introductionmentioning
confidence: 99%
“…Los datos obtenidos fueron procesados mediante el paquete estadístico RStudio Team (2020) en donde se realizó un análisis de varianza y prueba de comparación de medias de Tukey a una significancia de p<0.05 (Misgana et al, 2018) además de análisis de multivariado de agrupamiento (Cosme-De La Cruz et al, 2020) para conocer la relación entre las variables sobre el índice de área foliar.…”
Section: Análisis De Los Datosunclassified